John Cage [videorecording (DVD)] : journeys in sound - Miller, Allan, 1933-; Smaczny, Paul; Smaczny, Paul; Cage, John; Tudor, David, 1926-1996; Schleiermacher, Steffen; Cage, John; Cage, John; Cage, John; Cage, John (Accentus Music, 2012)
Documentary tribute to American avant-garde composer, John Cage; filmed in the U.S., Germany, and Japan, the program premieres rare archival footage, concert excerpts, and a set of short episodes featuring associates of Cage and contemporary artists.